2014
DOI: 10.1097/qad.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Lower adiponectin is associated with subclinical cardiovascular disease among HIV-infected men

Abstract: Objective To examine if altered levels of adipokines, adipose-derived peptides associated with myocardial infarction in the general population, may contribute to subclinical coronary atherosclerosis in HIV-infected persons. Design Nested cohort study. Methods We studied HIV-infected(HIV+) and HIV-uninfected(HIV−) men in the Multicenter AIDS Cohort Study with noncontrast CT to measure coronary artery calcium and regional adiposity; 75% additionally underwent coronary CT angiography to measure plaque composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
(35 reference statements)
2
27
2
Order By: Relevance
“…In other words, these markers are not associated with the early stages of atherosclerosis, but are related to a more advanced stage, namely, coronary artery stenosis. These findings are consistent with the results of our previous analyses on the relationship of adiponectin and circulatory markers of monocyte activation with CT scan findings in the MACS population …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, these markers are not associated with the early stages of atherosclerosis, but are related to a more advanced stage, namely, coronary artery stenosis. These findings are consistent with the results of our previous analyses on the relationship of adiponectin and circulatory markers of monocyte activation with CT scan findings in the MACS population …”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with the results of our previous analyses on the relationship of adiponectin and circulatory markers of monocyte activation with CT scan findings in the MACS population. 44,55 The biomarkers of inflammation and coagulation included in this study are widely used to represent different domains of inflammation (systemic mediators, endothelial cell activation, TNF-a-mediated immune cell activation, and acute phase response proteins) and coagulation, and the generally positive associations suggest widespread involvement of many facets of inflammation in HIV-mediated atherosclerosis. Some of these markers are widely available for clinical use, and have been suggested by other studies to be related to clinical CAD in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…65 Lower adiponectin levels have been associated with increased coronary artery calcification in HIV-infected men. 66 Our data suggest that telmisartan could affect FMD through nitric oxide release and inhibition of vasoconstriction. However, in our population with known CVD risk factors, simultaneous exposure to other drugs with anti-inflammatory properties (aspirin, statins, anti-hypertensive agents) could confound results, and our sample size was too small to fully adjust for concomitant anti-inflammatory medication use.…”
Section: Discussionmentioning
confidence: 63%
“…It also appears to correlate with subclinical cardiac disease as assessed by coronary reserve flow in HIV-infected subjects 30 . More recently, a larger study found that HIV-infected men had lower levels of adiponectin compared to HIV-uninfected men, and that these levels were inversely associated with increased coronary stenosis on CT angiography 31 . These observations have led to the hypothesis that adiponectin could serve as a novel predictor of cardiovascular risk as well as a potential target for pharmacologic intervention.…”
Section: Discussionmentioning
confidence: 99%